2000
DOI: 10.1046/j.1469-7580.2000.19630341.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional reconstruction of tetraploid↔diploid chimaeric mouse blastocysts

Abstract: Studies of tetraploid diploid (4n 2n) mouse chimaeras have demonstrated unequal contributions of 4n cells to different tissues of the midgestation conceptus. Such a pattern has also been reported in chimaeras as early as E3.5d, which show an enhanced contribution of 4n cells to the mural trophectoderm . In this study, sectioned 4n 2n and 2n 2n control chimaeric blastocysts were digitised and reconstructed in 3 dimensions (3-D). The 3-D images revealed only limited mixing of cells from the 2 contributin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…Everett and West [12] and Everett et al [13] reported that 4n-cells made a greater contribution to the TE than to the ICM of E3.5 chimeras; in the present experiments, however, we did not find a high population of 4n-cells in the TE of E3.5 chimeras (data not shown), and chimeric embryos did not eliminate 4n-cells until E4.5. The results of the BrdU incorporation assay revealed that the capabilities of cell division and DNA synthesis of 4n cells were almost the same as those of 2n-cells until the 4-cell-compaction stage.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Everett and West [12] and Everett et al [13] reported that 4n-cells made a greater contribution to the TE than to the ICM of E3.5 chimeras; in the present experiments, however, we did not find a high population of 4n-cells in the TE of E3.5 chimeras (data not shown), and chimeric embryos did not eliminate 4n-cells until E4.5. The results of the BrdU incorporation assay revealed that the capabilities of cell division and DNA synthesis of 4n cells were almost the same as those of 2n-cells until the 4-cell-compaction stage.…”
Section: Discussioncontrasting
confidence: 52%
“…Because of this characteristic of 4n-cells, tetraploid (4n) blastocysts are utilized as host embryos to produce embryonic stem cells that contribute effectively to the fetus [9][10][11]. Moreover, it has been reported that 4n↔2n-chimeric embryos display a restricted distribution of 4n-cells among the mural trophectoderm even at an embryonic age of 3.5 days (E3.5) [12,13], and the contribution of 4n-cells to 4n↔2n-embryos decreases from E3.5 to E4.5 [14].…”
mentioning
confidence: 99%
“…2B in Chroscicka et al, 2004). Such an extraordinarily high rate of seemingly precocious breakdown of coherent clonal growth, particularly in the trophectoderm lineage, has not been reported in previous lineage studies on either standard conceptuses or morula aggregation chimeras (Garner and McLaren, 1974; Pedersen et al, 1986; Dvorak et al, 1995; Gardner, 1997; Everett et al, 2000). Consequently, the possibility that it may relate to the injection‐related depression of cell number needs to be considered.…”
Section: Mapping Of the First Cleavage Plane On The Blastocystmentioning
confidence: 71%
“…The tendency of tetraploid cells to colonize the trophectoderm occurs at the blastocyst stage. This colonization may be accompanied by selection against tetraploid cells in the ICM, although at 4.5 days of development, the tetraploid cells may still be present at levels of 13% West, 1996, 1998;Everett et al, 2000). At days 7.5, 10.5, 12.5, 13.5, 16.5, and 17.5 of development, the tetraploid cells are observed to contribute to progressively smaller amounts of the ICM-derived tissues (Tarkowski et al, 1977;Nagy et al, 1990;James et al, 1995;Wang et al, 1997;Tang and West, 2000;Goto et al, 2002).…”
Section: Development Of 4n:2n Chimerasmentioning
confidence: 99%